Molecular characterisation of the GdhA- derivative of Pasteurella multocida B:2 - Muhammad Azam, Farahani; Saad, Mohd Zamri; Abdul Rahim, Raha; Chumnanpuen, Pramote; E-kobon, Teerasak; Othman, Sarah (Universiti Putra Malaysia Press, 2021)
Pasteurella multocida B:2 is an important veterinary pathogen causing fatal and acute haemorrhagic septicaemia (HS) in bovine. A live vaccine candidate, P. multocida B:2 GDH7 was reported to enable protection in cattle and buffaloes via intranasal (i. n.) administration. This potential vaccine was also reported to be self-transmitted from the vaccinated animal to the free-ranging animals allowing wider vaccination coverage. Prior to commercialisation, this potential vaccine requires further characterisation in accordance with the authoritative guidelines from the World Organisation for Animal Health (OIE). Hence, in this study, the potential vaccine strain, P. multocida B:2 GDH7 and the virulent parent strain were characterised through genomic and proteomic profiling. A crucial first step was to develop a sensitive yet simple and robust identification test to differentiate both strains which has been achieved by the development of a precise yet straightforward PCR method. In genomic profiling, Repetitive Extragenic Palindromic sequence-PCR (REP-PCR) was manipulated and both strains have a different display of genomic DNA band patterns. Some of the major OMPs were observed and prominent immunogens of P. multocida, OmpA and OmpH were observed to be expressed differently between these strains through SDS-PAGE analysis. In conclusion, a reproducible PCR detection method has enabled differentiation of both strains. Further characterisation of these strains shows a significantly different profile through genomic and proteomic profiling.